Condicionamento fisiológico de sementes de mamona como meio de atenuar os efeitos do estresse salino na germinação e estabelecimento da plântula. - Lopes, Lineker de Sousa (2013)
Castor bean (Ricinus communis) is a rise culture that needs production techniques appropriate to its growth conditions and niche market. Several researches have been conduct to adapt its development in the North and Northeast regions of the Brazil, which are regions with increase salinity problem. Thus, the seed and seedling salinity effects characterization and the evaluation of seed priming techniques can reduce the replanting costs and improve emergency uniformity, preparing the plant to response the salt stress. The overall objective of the research was to characterize the deleterious effects of salinity on castor bean seeds and evaluate the use of the techniques of seed priming as a means of minimizing them. Salinity affected the germination of castor bean cv. Energy only from the osmotic potential (Ψs) of -0.4 MPa, but seedling growth was affect under Ψs of -0.16 MPa. The water imbibition curve by the seed under salinity was decelerate with time of exposure to salinity. The enzymatic activity of superoxide dismutase are independent of salinity, while catalase and ascorbate peroxidase was responsive to salinity. There were no detectable enzyme activity of guaiacol peroxidase in the seeds of castor bean. However, despite osmopriming with CaCl2, NaNO2 and PEG-6000, tested under saline conditions, have shown good results, most notably the priming was NaNO3, this being the most recommended as priming to castor bean seeds.